Acoustic Voice Modifications in Individuals with Parkinson Disease Submitted to Deep Brain Stimulation - Romann, Aline Juliane; Beber, Bárbara Costa; Cielo, Carla Aparecida; Rieder, Carlos Roberto de Mello (International Archives of Otorhinolaryngology, 2019)
Introduction Subthalamic nucleus deep brain stimulation (STN-DBS) improves motor function in individuals with Parkinson disease (PD). The evidence about the effects of STN-DBS on the voice is still inconclusive.Objective To verify the effect of STN-DBS on the voice of Brazilian individuals with PD.Methods Sixteen participants were evaluated on the Unified Parkinson Disease Rating Scale—Part III, and by the measurement of the acoustic modifications in on and off conditions of stimulation.Results The motor symptoms showed significant improvement with STN-DBS on. Regarding the acoustic measures of the voice, only the maximum fundamental frequency (fhi) showed a statistical difference between on- and off-conditions, with reduction in off-condition.Conclusion Changes in computerized acoustic measures are more valuable when interpreted in conjunction with changes in other measures. The single finding in fhi suggests that DBS-STN increases vocal instability. The interpretation of this result should be done carefully, since it may not be of great value if other measures that also indicate instability are not significantly different.
Keywords: voice; acoustic analysis; deep brain stimulation; parkinson disease